Stability study of royal jelly in alginate-pectin beads - Muhammad Fitri Azhar; Nurul Ain Mohammad Hamdi; Muhammad Salahuddin Haris (IIUM Press, International Islamic University Malaysia, 2023)
Introduction: The stability of royal jelly (RJ) beads is a critical aspect to ensure the product is safe, efficacious, and possesses an acceptable quality for consumers. This study aims to establish storage duration and condition to ensure the stability of RJ in alginate-pectin beads. Methods: In this study, two types of packaging material have been chosen, namely polyethylene (PET) opaque bottles and glass containers. Samples of RJ beads were stored in four different storage conditions that include freezer, laboratory environment, real-time (30 °C, 75% RH) and accelerated (40 °C, 75% RH) stability chambers at different sampling points (0, 14 days, 1 month, 3 months). The RJ beads were characterised for physicochemical properties and 10-hydroxy-2-decenoic acid (10-HDA) content in the RJ-encapsulated beads. Results and discussion: The colour of RJ beads in the refrigerator remained whitish grey throughout the study but colour change in room temperature (laboratory) is observable starting from 1-month time point. The particle size of RJ beads stored in accelerated stability chamber had a decreasing pattern with significance (p < 0.05) for both different types of storage container. No significant difference (p > 0.05) between sphericity coefficient values of RJ beads stored in glass and PET container in refrigerator, room temperature and real-time stability chamber at 0 month and 14-day time point. Constant peaks of 10-HDA appeared for RJ samples stored in all storage conditions at 14-day time point. Nonetheless, at 1-month and 3-months, peak area starts to show decreasing trend for beads stored in room temperature, real time and accelerated stability chambers. Conclusion: The study showed that the RJ beads exhibited convincing stability for 3 months